2023
DOI: 10.3390/diagnostics13050857
|View full text |Cite
|
Sign up to set email alerts
|

MRI Radiomics and Predictive Models in Assessing Ischemic Stroke Outcome—A Systematic Review

Abstract: Stroke is a leading cause of disability and mortality, resulting in substantial socio-economic burden for healthcare systems. With advances in artificial intelligence, visual image information can be processed into numerous quantitative features in an objective, repeatable and high-throughput fashion, in a process known as radiomics analysis (RA). Recently, investigators have attempted to apply RA to stroke neuroimaging in the hope of promoting personalized precision medicine. This review aimed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…The same is true for the median RQS value, which was found to be 10 in our study, comparable to values shown by other published systematic reviews. Such examples include a maximum of 22 in studies of hepatocellular carcinoma [ 49 ] and a maximum of 16 in studies of ischemic strokes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for the median RQS value, which was found to be 10 in our study, comparable to values shown by other published systematic reviews. Such examples include a maximum of 22 in studies of hepatocellular carcinoma [ 49 ] and a maximum of 16 in studies of ischemic strokes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such measures may allow future clinicians to determine disease severity earlier in the management of IS patients. Multiple studies have demonstrated efforts to develop ML algorithms that can predict functional outcomes at various stages post-discharge (Forkert et al, 2015;Dragoș et al, 2023;Ozkara et al, 2023). Although the success of these studies is somewhat limited, it shows great promise for the future of IS care.…”
Section: Prognostication Of Ischemic Strokementioning
confidence: 99%
“…Despite the detailed content, it did not address the prognosis of stroke patients, which is precisely the focal point of concern for most clinical professionals and patients. Ragoș et al ( 13 ) summarized the evaluation of ischemic stroke outcomes using MRI radiomics and predictive models. However, relying solely on radiomic evaluation is too narrow, and the described imaging methods are not comprehensive enough.…”
Section: Introductionmentioning
confidence: 99%